Ovariectomy by laparotomy, a video-assisted approach or a complete laparoscopic technique in Santa Ines sheep - Teixeira, P. P. M. [UNESP]; Padilha, L. C.; Motheo, T. F.; Silva, M. A. M.; Oliveira, M. E. F.; Silva, A. S. L. DA; Barros, F. F. P. C.; Coutinho, L. N.; Flores, F. N.; Lopes, M. C. S.; Rodrigues, L. F. S.; Vicente, W. R. R. (Elsevier B.V., 2011)
The aim of the study was to compare the use of open ovariectomy, to the video-assisted laparoscopic approach or total laparoscopic ovariectomy in Santa Ines ewes. Surgical time and body weight gain/loss were recorded and post-surgical pain assessed using a behavioral scale. Laparotomy involved a longer surgical time (75 +/- 29.5 min), than the video-assisted (37.5 +/- 13.04 min; p < 0.05) or total laparoscopic approach (27.5 +/- 2.89; p < 0.01). Behavioral pain recorded score was higher for the laparotomy ovariectomy (5.6 +/- 0.5), compared to the video-assisted (0.3 +/- 0.5) and laparoscopic approaches (0.3 +/- 0.5) (p < 0.0001). No significant differences were recorded regarding body weight gain/loss during the first 30 days post-surgery, between the techniques. The video-assisted laparoscopic and total laparoscopic techniques of ovariectomy showed a tendency to have more advantages than the use of laparotomy as such. Less surgical trauma, a shorter surgical time, minimal post-surgical stress and better surgical recovery being highlighted as the main advantages of the endoscopic approaches in sheep. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Sheep; Ovariectomy; Video-assisted; Laparoscopy; laparotomy